(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Ba1-xPbxFe12O19 composition (x=0.0 to 1.0) synthesized by Co-precipitation and Sol-Gel methods. In Coprecipitation method BaCO3, PbO and Fe (NO3)3 .9H2O were used as basic ingredients. Acids and Di-H2O were used as solvents. Molar ratio of cations was 12. pH of solution kept constant at 13. All samples sintered at 965±5oC for three hours. Lead own properties, synthesis at room temperature and substitution in R-block of structure were the reasons for decrease of phase purity from ?x? =0.0 to 70% for ?x?=1.0. Decrease in phase purity and heterogeneity of material caused the properties to decrease. In Sol gel method, Nitrates (salts) and Ethylene glycol (liquid) were the basic material used. The mixed solutions dried out on a hot plate whose temperature was maintained constant at 200±2oC. Pellets formed by applying suitable hydraulic pressure and then sintered at same temperature written above i.e. 965±5oC for three hours. 100% phase purity achieved. All properties modified. Temperature and frequency dependent electrical properties investigated and reported here. DC and AC obtained properties were useful for different electronics and computer devices like capacitors, smart storage devices and multilayer chip inductors. Overall, both these properties improved through solgel method as compared to co-precipitation method. It was because of improvement in phase purity and change in morphology of synthesized material.